Corals adapted to extreme and fluctuating seawater pH increase calcification rates and have unique symbiont communities - Tanvet, Clément; Camp, Emma F.; Sutton, Jill; Houlbrèque, Fanny; Thouzeau, Gérard; Rodolfo‐Metalpa, Riccardo (Ecology and evolution, 2023)
Ocean acidification (OA) is a severe threat to coral reefs mainly by reducing their calcification rate. Identifying the resilience factors of corals to decreasing seawater pH is of paramount importance to predict the survivability of coral reefs in the future. This study compared corals adapted to variable pHT (i.e., 7.23–8.06) from the semi‐enclosed lagoon of Bouraké, New Caledonia, to corals adapted to more stable seawater pHT (i.e., 7.90–8.18). In a 100‐day aquarium experiment, we examined the physiological response and genetic diversity of Symbiodiniaceae from three coral species (Acropora tenuis, Montipora digitata, and Porites sp.) from both sites under three stable pHNBS conditions (8.11, 7.76, 7.54) and one fluctuating pHNBS regime (between 7.56 and 8.07). Bouraké corals consistently exhibited higher growth rates than corals from the stable pH environment. Interestingly, A. tenuis from Bouraké showed the highest growth rate under the 7.76 pHNBS condition, whereas for M. digitata, and Porites sp. from Bouraké, growth was highest under the fluctuating regime and the 8.11 pHNBS conditions, respectively. While OA generally decreased coral calcification by ca. 16%, Bouraké corals showed higher growth rates than corals from the stable pH environment (21% increase for A. tenuis to 93% for M. digitata, with all pH conditions pooled). This superior performance coincided with divergent symbiont communities that were more homogenous for Bouraké corals. Corals adapted to variable pH conditions appear to have a better capacity to calcify under reduced pH compared to corals native to more stable pH condition. This response was not gained by corals from the more stable environment exposed to variable pH during the 100‐day experiment, suggesting that long‐term exposure to pH fluctuations and/or differences in symbiont communities benefit calcification under OA. This paper investigated the physiological response and genetic diversity of Symbiodiniaceae from three coral species originating from both a stable and a fluctuating pH environment and cultured under four pH conditions for 100 days. We identified higher calcification rates and unique symbiont community for corals from the fluctuating environment. The long‐term exposure to environmental variability is thought to increase coral plasticity to the ongoing rapid ocean acidification.